Analisis Pelaksanaan Pelatihan Wicara Publik bagi Anak Usia Dini di Rumah Tahfidz Yatim Dhuafa - Amir Hamzah; Reno Susanto; Clara Rizky Amelia; Deo Andika Saputra; Marviansyah .; Nayla Lovina Sandra (CV. ITTC INDONESIA, 2026)
This research aims to analyze the implementation of public speaking training for early childhood at Rumah Tahfidz Yatim Dhuafa within the Community Service Program (KKN) of UIN Raden Fatah Palembang students. This research uses a qualitative method with a descriptive approach thru observation, interviews, and documentation techniques. The research results show that public speaking training, which includes speeches and short lectures, storytelling of prophets' tales and Indonesian folk tales, as well as sharing daily life experiences, can enhance the speaking courage, self-confidence, and communication skills of early childhood children. Although there were some obstacles during the implementation of the activities, the KKN students were able to apply interactive and enjoyable teaching methods, allowing the program to run smoothly. Thus, public speaking training can be an alternative for developing soft skills in early childhood within the context of religious education.